2022
DOI: 10.1177/1356336x221115376
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of content development in physical education: Preschool teachers’ selection of instructional tasks

Abstract: In recent years, attention has been placed on dimensions of instructional quality. One critical element of this quality in preschool physical education (PE) is teachers’ ability to present content in a way that facilitates learning. This study aimed to describe the development of the content in PE in preschool. Participants in the study were 11 preschool teachers. Data were collected using systematic observations. Specifically, a modified version of the Task Structure System was used to observe three 40-minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…The case above is not unique among sports exercise science students; many others have similar misunderstandings about physical education. Other research has also shown that in-service and pre-serve teachers contain misconceptions about their future beliefs about how to teach PE [2] . They cause problems for students in learning movement techniques and can result in misunderstanding the concepts taught.…”
Section: Introductionmentioning
confidence: 99%
“…The case above is not unique among sports exercise science students; many others have similar misunderstandings about physical education. Other research has also shown that in-service and pre-serve teachers contain misconceptions about their future beliefs about how to teach PE [2] . They cause problems for students in learning movement techniques and can result in misunderstanding the concepts taught.…”
Section: Introductionmentioning
confidence: 99%
“…Physical education (PE) teachers strive to improve their pedagogical content knowledge (PCK) to provide the most effective instruction for their students [1][2][3]. While inservice PE teachers may have a basic understanding of the different types of sports activities due to their common knowledge (CK), they still need to acquire advanced specialized content knowledge (SCK) to instruct their students efficiently [4][5][6].…”
Section: Introductionmentioning
confidence: 99%